Protection of Hesperidin against Methotrexate-Induced Nephrotoxicity may be Mediated by Nrf2/HO-1 Pathway - Morsy, Mohamed Aly; El-Sheikh, Azza Ali Kamel; Ibrahim, Ahmed Ragaa Nour; El-Daly, Mahmoud (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Methotrexate (MTX), a successfully used chemotherapeutic in the treatment of various malignancies and autoimmune diseases, might cause severe nephrotoxicity. Here, we aimed at investigating possible nephroprotective effects of hesperidin (HES), a flavanone present in citrus fruits, against MTX-induced toxicity. Methods: Rats were divided into control, HES, MTX, and MTX/HES groups, where HES was administered in a dose of 100 mg/kg/day orally for 8 days and MTX in a single i.p. dose of 20 mg/kg on day 5 of the experiment. Results: Pretreatment with HES significantly improved MTX-induced deteriorated kidney function and structure, as well as reversed MTX effects on renal tumor necrosis factor (TNF)-α level and caspase 3 expression. MTX upregulated renal breast cancer resistance protein (BCRP); an efflux transporter that extrudes MTX from the kidney. Unfortunately, MTX/HES did not show a further increase in BCRP expression but rather showed downregulation. MTX also caused downregulation of renal nuclear factor erythroid 2-related factor 2 (Nrf2) and hemeoxygenase-1 (HO-1) expressions, whereas HES reversed the MTX effect and upregulated renal Nrf2/HO-1. Conclusion: HES conferred protection against MTX-mediated nephrotoxicity, at least in part via anti-inflammatory and anti-apoptotic mechanisms. Nrf2/HO-1 pathway, but not BCRP, may have a role in HES-induced nephroprotection against MTX toxicity.
Keywords: Methotrexate; Hesperidin; Nrf2; HO-1; TNF-α; Caspase 3; BCRP